2008
DOI: 10.1021/ol8010858
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Hydroamination of Allenes with N-Unsubstituted Carbamates Catalyzed by a Gold(I) N-Heterocyclic Carbene Complex

Abstract: Reaction of 2,3-pentadienyl benzoate and benzyl carbamate with a catalytic 1:1 mixture of (NHC) AuCl and AgOTf in dioxane at 23 °C for 5 h led to isolation of (E)-4-(benzyloxycarbonylamino)-2-pentenyl benzoate in 84% yield as a single regio-and diastereomer. Gold(I)-catalyzed hydroamination was effective for a number of N-unsubstituted carbamates and a range of substituted allenes.Allylic amines are components of many naturally occurring and biologically active molecules and are versatile building blocks for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 64 publications
0
58
0
Order By: Relevance
“…Espinet showed that acyclic carbenes can be used as ligands for Au(I) to realize intramolecular hydrocarbamation [240], while Widenhoefer has used the commercially available 1,3-bis[(2,6-diisopropylphenyl)imidazole-2-ylidine] (IPr) NHC in combination with cationic Au(I) to realize regioselective intermolecular hydroamination of 1,1-disubstituted allenes with benzyl carbamate to access allylamines with quaternary centers adjacent to N. This same catalyst can also accommodate 1,3-disubstituted allenes and even tetrasubstituted allenes (Table 15.19) [241]. Interestingly, these products are in contrast to the preferred products accessed with related Au(I)-phosphine complexes in combination with aniline substrates (Table 15.18) [239].…”
Section: Catalysts For Allene Substratesmentioning
confidence: 99%
“…Espinet showed that acyclic carbenes can be used as ligands for Au(I) to realize intramolecular hydrocarbamation [240], while Widenhoefer has used the commercially available 1,3-bis[(2,6-diisopropylphenyl)imidazole-2-ylidine] (IPr) NHC in combination with cationic Au(I) to realize regioselective intermolecular hydroamination of 1,1-disubstituted allenes with benzyl carbamate to access allylamines with quaternary centers adjacent to N. This same catalyst can also accommodate 1,3-disubstituted allenes and even tetrasubstituted allenes (Table 15.19) [241]. Interestingly, these products are in contrast to the preferred products accessed with related Au(I)-phosphine complexes in combination with aniline substrates (Table 15.18) [239].…”
Section: Catalysts For Allene Substratesmentioning
confidence: 99%
“…1-Alkylallenes, 1,1-, and 1,3-disubstituted allenes also underwent gold(I)-catalyzed hydroamination with morpholine, albeit with diminished efficiency and/or regioselectivity. Widenhoefer has reported the intermolecular hydroamination of allenes with Nunsubstituted carbamates catalyzed by a gold(I) N-heterocyclic carbene complex [41]. For example, reaction of 3-methyl-1,2-butadiene 57 with benzyl carbamate catalyzed by a 1 : 1 mixture of (IPr)AuCl and AgOTf in dioxane at 23 C for 24 h formed benzyl 1,1-dimethyl-2-propenylcarbamate in 93% isolated yield as a single regioisomer resulting from attack of benzyl carbamate at the more hindered terminus of 57 (Eq.…”
Section: Intermolecular Processesmentioning
confidence: 99%
“…[11] Our initial studies focused on the reaction of diene 1 with catalytic amounts cationic gold(I) complexes (see the Supporting Information for a complete list). While attempts to catalyze the reaction with triphenylphosphinegold(I) did not produce appreciable amounts of pyrrolidine (Table 1, entry 1), we were pleased to find that the combination of (R)-DTBM-SEGPHOS(AuCl) 2 (5) and AgBF 4 in dichloromethane gave pyrrolidine 2 exclusively in 5 % conversion after 24 hours (entry 2). After examining a variety of protecting groups on the nitrogen atom, we found that the Mbsprotected (Mbs = p-methoxy benzenesulfonyl) amine gave a small enhancement in reactivity (entry 3).…”
mentioning
confidence: 96%
“…[1,2] While significant progress has been made in the asymmetric hydroamination of allenes, enantioselective goldcatalyzed hydroamination of simple alkenes and dienes has been limited to reactions in which urea is employed as a nucleophile. [3] Furthermore, as simple Brønsted acids are also known to be effective catalysts for alkene hydroamination [4] and gold(I) triflates are often employed in olefin activation, [5] the role of gold in these reactions is unclear. In 2009, we found that, in presence of stoichiometric amounts of base, alkylgold(I) complexes could be formed by gold-promoted addition of nitrogen nucleophiles to unactivated alkenes [Eq.…”
mentioning
confidence: 99%